2006
DOI: 10.1007/s00508-005-0502-0
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Meningokokkenerkrankungen in Österreich 2002: Überprüfung der Datenqualität durch Vergleich zweier Datenquellen

Abstract: All probable cases of meningococcal disease, even those (still) lacking microbiological confirmation, should be reported to the public health authorities as soon as possible, in order to ensure the necessary prompt prophylactic action (e.g., chemoprophylaxis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…We performed an evaluation of the completeness of N. meningitidis reporting using the capture–recapture method. Unadjusted and adjusted (for ICD-9 coding mistakes discovered in the post-hoc analysis) estimates of completeness were lower than European studies that only evaluated confirmed cases over a similar time period [13, 14]. De Greef et al .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We performed an evaluation of the completeness of N. meningitidis reporting using the capture–recapture method. Unadjusted and adjusted (for ICD-9 coding mistakes discovered in the post-hoc analysis) estimates of completeness were lower than European studies that only evaluated confirmed cases over a similar time period [13, 14]. De Greef et al .…”
Section: Discussionmentioning
confidence: 90%
“…The assumptions of equal chance of capture and independence of data sources are often the greatest concerns when using the capture–recapture method to analyse epidemiological data [ 9 ]. In our study, however, the sources of data arise from separate and distinct healthcare functions [ 13 ]. Surveillance reports arise from the clinical evaluation of patients from hospital personnel who are required to report suspected, probable, and confirmed cases of IMD.…”
Section: Discussionmentioning
confidence: 99%
“…Asplenic patients have an increased risk of overwhelming infections with encapsulated bacteria such as Haemophilus influenzae, Neisseria meningitidis and Streptococcus pneumoniae [1,2]. The predominant organism is S. pneumoniae, which is still associated with high mortality despite appropriate antimicrobial therapy and intensive care support [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, population surveillance for and monitoring of infectious disease outbreaks requires real time clinical information. [5-11] Similarly, coordination during natural disasters also benefits from timely exchange of clinical data, as seen during Hurricane Katrina in 2005. [12,13]…”
Section: Introductionmentioning
confidence: 99%